AN INSIGHT INTO BLOG USE IN EFL READING CLASS - Santiana Santiana; Rachmatia Fajrina Faisal; Melisa Sri (International Journal of Educational Best Practices, 2023)
This study was performed concerning the usage of a blog to ascertain the perceptions of the students regarding the usage of blogs in Extensive Reading (hereafter ER) classes at one of Tasikmalaya’s universities. Braun and Clarke’s Descriptive Case Study Design and Thematic Analysis techniques were used in this study. The primary data source was semi-structured interviews with four participants, transcribed and analysed using Thematic Analysis. This study discovered that blogging has advantages and disadvantages in the ER class. The advantage of using blogs as media in Extensive Reading classes is that blogging is easy to use and can increase student creativity. Furthermore, blogging can increase student motivation to read, serve as a forum for reflection, and increase learning autonomy. However, based on the findings, it turns out that there are some disadvantages to using blogs as media in Extensive Reading classes, such as limited access to blogs, sluggish connectivity for submitting assignments, and causing time-consuming problems. Finally, the research provides information to lecturers so that lecturers can learn about the benefits and drawbacks of using blogs in ER learning.